Facilitating self-development of children in ballet education (2012)
M. Ed. === We live in an era of technology where people strive for technological precision and higher standards of living. We can describe this as the information era where it is no longer possible to expect from learners to memorise all given information. Apart from that, we live in a multi-cultural society which leads to unique considerations that have to be accommodated. We are faced with a variety of problems such as economic instability, corruption and crime. An allover result of such conditions could cumulate in problems with discipline. The school is only one of the entities in the total process of learning and current changes in the educational system focus on the responsibility to enrich the child with life-long learning habits. Learning opportunities outside schools are encouraged to enhance self-development and learning. This study aims to explore and describe the life-world of the classical principal dancer in order to gain an understanding of what it takes to become a top performer. The qualities that support educational development and self-development will be outlined. An explorative, descriptive, contextual and qualitative study was carried out with the view to obtain insight and understanding with regard to the classical principal dancer's life-world, what it takes to perform and to reach the top. The research is conceptulised and focuses on principal dancers of the South African Ballet Theatre and the Cape Town City Ballet. The phenomenological interviewing method was used as well as the taking of field notes. The interviews were audio taped and then transcribed. The researcher made use of Tesh's method to process the data. Guba's model was applied to ensure trustworthiness of the research.